Safety evaluation of the food enzyme alpha-amylase from a genetically modified bacillus licheniformis (strain NZYM-AN) - EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) (2018)
The food enzyme is an α-amylase (4-α-d-glucan glucanohydrolase; EC 3.2.1.1) produced with a genetically modified Bacillus licheniformis strain NZYM-AN by Novozymes A/S. The genetic modifications do not give rise to safety concerns. The food enzyme does not contain the production organism or recombinant DNA; therefore, there is no safety concern for the environment. The α-amylase is intended to be used in starch processing for the production of glucose syrups and distilled alcohol production. Residual amounts of total organic solids (TOS) are removed by distillation and by the purification steps applied during the production of glucose syrups (by > 99%). Consequently, dietary exposure was not calculated. Genotoxicity tests with the food enzyme did not raise a safety concern. The amino acid sequence of the food enzyme did not match to those of known allergens. The Panel considered that under the intended condition of use, the risk of allergic sensitisation and elicitation reactions upon dietary exposure to this food enzyme cannot be excluded, but the likelihood is considered low. Based on the microbial source, the genetic modifications, the manufacturing process, the compositional and biochemical data, the removal of TOS during the intended food production processes and the findings in the genotoxicity studies, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.